LANGUAGE LEARNING STYLES USED BY STUDENTS OF BASIC ENGLISH COURSE (BEC) PARE - HIDAYAH, ULFA NURUL (Jurnal Ilmiah Mahasiswa FIB, 2013)
Learning styles are the important factors to help students to learn a second or foreign language. A learning habit of every individual is needed to support the student’s learning to be more effective, for example by taking an English course. Learning styles can be classified into: visual, auditory, kinesthetic, tactile, group, and individual. This study is conducted to examine the language learning styles applied by the students of Basic English Course (BEC) in Pare, Kediri. This study applies descriptive quantitative approach, aimed at describing the learning styles of BEC students. The subjects of this study are eighty students of Basic English Course taken by random sampling. The data were taken using Perceptual Learning Style Preferences (PLSP) questionnaire, designed by Joy M. Reid. Every number of learning styles is classified into three categories, namely: major, minor, and negligible learning style preferences. The result of this study reveals that the most preferred language learning styles are auditory major learning style which falls into the highest score to the lowest score are auditory with the mean score of 60%, kinesthetic with the mean score of 57.5%, group with the mean score of 57.5%, tactile with the mean score of 47.5%, individual with the mean score of 43.9%, and visual learning style with the mean score of 21.5%. From this study, it can be concluded that every student learns based on their own learning style and has different learning styles which can support their progress in learning. In suggestions, it is expected that the institution can add some facilities to support the learning process for example English LAB. For the students, it can be more effective if they always be consistent listening the material and focus on hearing the teacher’s explanation. For the teachers, they can help students in understanding their learning styles, and for the next researchers can analyze with other measurements and the other model of learning styles to measure students’ success. Keywords: learning styles, Training Class (TC) program , PSLP questionnaires.